"GEOPARK CILETUH" (IDENTIFICATION OF LOCAL WISDOM / CULTUREDIVERSITY AND BIODIVERSITY / BIODIVERSITY AS MEDIA AND LEARNING RESOURCES ON IPS SD (International Conference on Elementary Education, 2018)
Geopark Ciletuh one of its territory is located in Tamanjaya village, Ciemas district, Sukabumi district, West Java. Geographically, the village of Tamanjaya is divided into two regions, namely the land area and the mainland with the laus wilaya 1,372,5 Ha (Tamanjaya, 2015) and the population of 6,500 people (Statistik Daerah, 2015). Such conditions can be utilized by the local community as one way to improve the economy of the region, with various businesses such as SMEs, back packers, creative industries, tourism and so forth, especially if the village area Tamanjaya serve as Geopark by UNESCO in 2020 later. However, the potential that is currently not oriented and contribute to the world of education such as media and learning resources in elementary schools such as IPS material about Indonesia's natural state and cultural diversity of Indonesia. This research approach using qualitative descriptive research method. Descriptive qualitative research is a study that describes or describes the existing phenomena, both natural phenomena or human engineering (Sukmadinata, 2008).